Solar Radiation as an Isolated Environmental Factor in an Experimental Mesocosm Approach for Studying Photosynthetic Acclimation of Macrocystis pyrifera (Ochrophyta) - Celis-Plá, Paula S. M.; Kappes, José Luis; Figueroa, Félix L.; Pereda, Sandra V.; Villegas, Karina; Altamirano, Robinson; Hernández-González, María Carmen; Buschmann, Alejandro H. (Frontiers in Plant Science, 2021)
Solar radiation effects on the ecophysiology and biochemical responses of the brown macroalga Macrocystis pyrifera (L.) C. Agardh were evaluated using a mesocosm approach in Southern Chile. Treatments with different radiation attenuations were simulated with three vertical attenuation coefficients: (1) total (Kd = 0.8 m−1), (2) attenuated (Kd = 1.2 m−1), and (3) low (Kd = 1.6 m−1) radiation levels. Nutrient concentration and temperature did not show differences under the three light conditions. Photosynthetic activity was estimated by in vivo chlorophyll a (Chla) fluorescence under the three light treatments as an isolated physical factor in both in situ solar radiation in the field. This was achieved using a pulse amplitude-modulated (PAM) fluorometera—Diving PAM (in situ). Photosynthetic activity and biochemical composition were measured in winter during two daily cycles (1DC and 2DC) in different parts of the thalli of the plant: (1) canopy zone, (2) middle zone, and (3) down zone, associated with different depths in the mesocosm system. Nevertheless, the in situ electron transport rate (ETRin situ) was higher in the exposed thalli of the canopy zone, independent of the light treatment conditions. The concentration of phenolic compounds (PC) increases in the down zone in the first daily cycle, and it was higher in the middle zone in the second daily cycle. The Chla increased in the morning time under total and attenuated radiation in the first daily cycle. Solar radiation increasing at midday prompted the photoinhibition of photosynthesis in the canopy zone but also an increase in productivity and phenol content. Therefore, light attenuation in the water column drove key differences in the photo-physiological responses of M. pyrifera, with the highest productivity occurring in thalli positioned in the canopy zone when exposed to solar irradiance.